Islam and the veil : theoretical and regional contexts - Gabriel, Theodore P. C.; Hannan, Rabiha (London ; New York : Continuum, 2011)
This volume is centred around the theme of veiling in Islam and provides multifarious aspects of the discussion regarding veiling of Muslim women, especially in the West. The issue of veiling has been intensively debated in Western society and has implications for religious liberty, inter-communal relationships and cultural interaction. Islam and the Veil seeks to generate open and objective discussion of this highly important, though controversial, subject, with contributions from distinguished scholars and academics, including female practitioners of Islam. This subject has inflamed passions and generated heated debate in the media in recent years, particularly in the West. This book aims to look at the historical background, theological and social factors underlying the veiling of women in Islam. Such discussion will provide the reader with a well-balanced and unbiased analysis of this important aspect of Islamic practice. -- Back cover.
Respect in a plural society / Marcus Braybrooke -- Reflections on sartorial injunctions in Islam / Theodore Gabriel -- Unveiling orientalism in reverse / Alison Scott-Baumann -- Mawdudi, purdah and the status of women in Islam / Roy Jackson -- Female seclusion and the veil : two issues in political and social discourse / Simonetta Calderini -- The veil? between tradition and reason, culture and context / Usama Hasan -- An exploration of the debates pertaining to head covering and face veiling of women in the British Muslim context / Rabiha Hannan -- Norms of gender interaction / Javaid Ghamidi -- Hijab, a symbol of modesty or seclusion? / Khola Hassan -- Marginalisation or an opportunity for dialogue? / Sariya Contractor -- The Islamic veil : a focal point for social and political debate / Malika Ghamidi -- Muslim women, the veil and activism / Rajnaara C. Akhtar -- Hijab and belonging-Canadian Muslim women / Katherine Bullock.
Select bibliography : p. [200]-202
Keywords: Hijab (Islamic clothing); Veils -- Islamic countries; Women in Islam; Muslim women -- Clothing; Islamic clothing and dress